2011
DOI: 10.1104/pp.111.173088
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Secondary Ion Mass Spectrometry Reveals the Contrasting Subcellular Distribution of Arsenic and Silicon in Rice Roots      

Abstract: Rice (Oryza sativa) takes up arsenite mainly through the silicic acid transport pathway. Understanding the uptake and sequestration of arsenic (As) into the rice plant is important for developing strategies to reduce As concentration in rice grain. In this study, the cellular and subcellular distributions of As and silicon (Si) in rice roots were investigated using high-pressure freezing, high-resolution secondary ion mass spectrometry, and transmission electron microscopy. Rice plants, both the lsi2 mutant la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 66 publications
5
91
3
Order By: Relevance
“…3G, Table 2 authors also showed that Fe plaque is composed of fine needles approximately10 nm 344 thick and 200 to 300 nm long, and this is why the Fe plaque does not appear as a sharp 345 line in the nanoSIMS images (Moore et al, 2011). This fact was also evident in our 346 study (Fig.3G), in which, using SEM-EDX analysis, a discontinuous Fe accumulation 347 was detected along the root surface.…”
Section: Iron Status Effect On Silicon Distribution In Rice Plants 314supporting
confidence: 67%
See 1 more Smart Citation
“…3G, Table 2 authors also showed that Fe plaque is composed of fine needles approximately10 nm 344 thick and 200 to 300 nm long, and this is why the Fe plaque does not appear as a sharp 345 line in the nanoSIMS images (Moore et al, 2011). This fact was also evident in our 346 study (Fig.3G), in which, using SEM-EDX analysis, a discontinuous Fe accumulation 347 was detected along the root surface.…”
Section: Iron Status Effect On Silicon Distribution In Rice Plants 314supporting
confidence: 67%
“…The large majority of the available information related to the localization of 92 Fe, Mn, Cu, Zn and Si in rice is focused on rice seeds using S-XRF (Lu et al, 2013). Moore et al, 2011). 103 6 mL HNO 3 (65%), 2 mL H 2 O 2 (30%), and 1 mL HF (40%), using a microwave (CEM 135…”
Section: Simplicity Other Techniques Such As Transmission Electron Mmentioning
confidence: 99%
“…Although the subcellular distribution of As was not examined in this study, the data suggest a role of the endodermis (and border cells) in limiting this movement of As from the roots to the shoots. These observations are somewhat similar to those reported for rice roots examined using nano-secondary ion mass spectrometry (Moore et al, 2011), in which the highest concentrations of As were in the endodermis, pericycle, and xylem parenchyma cells, with little accumulation in the cortex and rhizodermis. For rice, the accumulation of As may also occur at the exodermis (the outermost layer of the cortex), which serves as an apoplastic barrier (Hose et al, 2001;Zhao et al, 2009Zhao et al, , 2010.…”
Section: Resultssupporting
confidence: 75%
“…A limited number of studies have investigated As distribution in roots. For instance, Moore et al (2011) used nano-secondary ion mass spectrometry to investigate As distribution with subcellular resolution in cryosubstituted roots of rice. Hansel et al (2001) examined freeze-dried roots of Phalaris arundinacea (an aquatic species).…”
mentioning
confidence: 99%
“…A micrometric proteinaceous scaffold, which averaged 2 % C dry weight, could be detected in the siliceous structure (Müller et al, 2010). The NanoSIMS technique was also used for identifying silicification sites in rice roots (Moore et al, 2011 C] − ratio were also created. Line scans were drawn across the analyzed surfaces and ion intensity vs. distance along the line were plotted.…”
Section: Methodsmentioning
confidence: 99%